Metastatic Rhabdoid Meningioma with BRAF V600E Mutation and Good Response to Personalized Therapy: Case Report and Review of the Literature. (3rd April 2015) - Mordechai, Oz; Postovsky, Sergey; Vlodavsky, Eugene; Eran, Ayelet; Constantini, Shlomi; Dotan, Eynat; Cagnano, Emmanuela; Weyl-Ben-Arush, Myriam
Abstract : Rhabdoid meningioma is an aggressive phenotype of meningioma, associated with a poor prognosis. We present a very rare case of high-grade meningioma with rhabdoid features that eventually expressed in a coma state. Comprehensive genomic profiling using a Next Generation Sequencing (NGS) assay revealed three genomic alterations: activating BRAF mutation (V600E), loss of CDKN2A/2B, and APC I1307K. After treatment with BRAF inhibitor (dabrafenib), the child's clinical condition improved progressively. After seven months, an MEK inhibitor was added (trametinib).